Free to move foot voting and political freedom - Somin, Ilya (Oxford University Press, 2020)
Ballot box voting is often considered the essence of political freedom. But it has two major shortcomings: individual voters have only a tiny chance of making a difference, and they also have strong incentives to remain ignorant about the issues at stake. "Voting with your feet" is far superior on both counts. In Free to Move, Ilya Somin explains who expanding foot voting opportunities can greatly enhance political freedom for millions of people around the world. That applies to foot voting in federal systems, foot voting in the private sector, and especially foot voting through international migration. These three types of foot voting are rarely considered together. But Somin explains how they have major common virtues, and can be mutually reinforcing. Free to Move addresses a variety of objections to expanded migration rights, including claims that the "self-determination" of natives requires giving the power to exclude migrants, and arguments that migration is likely to have harmful side effects, such as undermining political institutions, overburdening the welfare state, increasing crime and terrorism, and spreading undesirable cultural values. While these objections are usually directed at international migration, Somin shows how a consistent commitment to such theories would also justify severe restrictions on internal freedom of movement. That implication is yet another reason to be skeptical of such arguments. The book also shows how both domestic constitutional systems and international law can be structured to increase opportunities for foot voting, while mitigating potential downsides of freedom of movement."--